Solve for x in the first equation, then solve the system using substitution. Write your answer as (x, y). 1103-03-02-00-00_v2_files/i

Question

Solve for x in the first equation, then solve the system using substitution. Write your answer as (x, y).
1103-03-02-00-00_v2_files/i0050000.jpg

0

Answers ( No )

    0
    2021-10-11T03:18:05+00:00

    2x – 6y = 14
    2x = 6y + 14
    x = 3y + 7…..so sub in 3y + 7 for x in the other equation

    4x – y = 9
    4(3y + 7) – y = 9
    12y + 28 – y = 9
    12y – y = 9 – 28
    11y = – 19
    y = -19/11

    x = 3y + 7
    x = 3(-19/11) + 7
    x = -57/11 + 7
    x = -57/11 + 77/11
    x = 20/11

    solution is : (20/11, -19/11) <==

Leave an answer

Browse
Browse